The Role of Educational Institutions in Enhancing India’s Pluralistic Identity - Kunzru, Aryaman (JOURNAL OF INDIAN EDUCATION, 2018)
The purpose of this paper is to analyse the effectiveness of educational institutions such as the National Council of Educational Research and Training (NCERT), when it comes to translating the values of India’s Constitution to younger generations—preserving the values of religious harmony, equality, and pluralism as enshrined in our Constitution. India’s educational institutions have a very important role to play in inculcating the right values among its young citizens, and they are a key player in driving India’s ability to nurture and strengthen religious harmony among the multitude of faith that call India home.